Comparison of Maternal and Perinatal Outcomes of Pregnancy with Systemic Lupus Erythematosus in Planned Referrals Compared to Emergency Referrals Based on the Maternal Fetal Triage Index at Dr. Kariadi General Hospital, Semarang, Indonesia - Gayuh Tunggal Rachmadhini; Rakhma Yanti Hellmi; Yuli Trisetiyono; Arufiadi Anityo Mochtar; Endy Cahyono; Ratnasari Dwi Cahyanti; Putri Sekar Wiyati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that attacks the skin and the musculoskeletal, kidney, neuropsychiatric, hematological, cardiovascular, pulmonary, and reproductive systems. In pregnancies with SLE, early referral to the hospital with the involvement of obstetricians and rheumatologists, and other specialists as needed, as well as individual management plans, regular reviews, and early recognition of flares and complications, are important. This study aimed to determine the differences in maternal and perinatal outcomes referred by planned referrals compared to emergency referrals, especially in pregnant patients with SLE. Methods: This study was an analytic observational study with a retrospective cohort approach. A total of 40 subjects participated in this study. Data analysis using SPSS software was carried out univariate and bivariate to examine the relationship between types of referrals and maternal and perinatal outcomes. Results: There were significant differences between the types of emergency referrals and planned referrals in the variable incidence of preeclampsia and SLE exacerbations. There were no significant differences between the types of emergency referrals and planned referrals on the variable incidence of lupus nephritis, maternal death, premature delivery, fetal growth restriction, fetal death, and the incidence of neonatal lupus syndrome. Conclusion: The incidence of severe preeclampsia and SLE exacerbation was lower in planned referrals compared to emergency referrals in pregnant patients with SLE at Dr. Kariadi General Hospital, Semarang, Indonesia.